The Advantage of Incumbency among Czech Mayors: Analysis of Election Results in the 128 Largest Cities in the Czech Republic - Čapek Jakub (Politics in Central Europe, 2025)
The incumbency effect, where incumbents have a higher likelihood of electoral success, is a well-documented phenomenon globally but remains under-researched in the Czech Republic. This article investigates whether and to what extent the incumbency effect is present among Czech mayors. Using a dataset of the 128 largest Czech cities by population (excluding Prague) and covering elections between 2002 and 2022, the study analyses the success of incumbent mayors in retaining their positions. The findings confirm that over 50% of mayors successfully defended their posts. The research also examines the dynamics of mayoral re-election, highlighting that first-time incumbents enjoy a notable advantage, which tends to diminish with each consecutive term. These results contribute to understanding the mechanics of incumbency in proportional electoral systems and offer directions for future research, including the exploration of causal relationships and the impact of socio-economic factors on re-election rates.